Predicting factors of sexually transmitted infection preventive behavior among adolescent in the era of Coronavirus 2019 pandemic - KhruangKaew, Patcharawan; Praditsathaporn, Chanita (Journal of health and health management, 2025)
A cross-sectional study was conducted to examine preventive behaviors against sexually transmitted infections (STIs), predisposing factors, reinforcing factors, enabling factors among adolescents during the COVID-19 pandemic and to identify predictive factors. The sample consisted of 428 students in grades 10-12 from a province in the upper northern region of Thailand, selected through multi-stage random sampling. The research instruments included three sets of questionnaires include: 1. A data on personal information 2. A questionnaire assessing enabling, predisposing, and reinforcing factors, 3. A questionnaire assessed STI prevention behaviors. All instruments were validated for content validity by a panel of three experts, with a reliability coefficient of STI prevention behaviors = .80, the knowledge regarding new lifestyle related to sexually =.72, the attitude score towards the prevention of sexually activity =.76, the sexually arousing media =.80, the accessibility of sexual health services = .87, the familial relationship =.86, and the parenting behavior =.74. Data were analyzed using descriptive statistics and multiple regression analysis with the enter method. The findings revealed that the prevention behaviors for STIs during the COVID-19 were at a moderate level. Accessibility to sexual health services and familial relationships predicted these prevention behaviors at a rate of 78.4%. This is recommended that nurses should develop health planning program to preventing sexually transmitted infections among high school students.